2016
DOI: 10.1088/1748-3190/11/4/046005
|View full text |Cite
|
Sign up to set email alerts
|

Self-propelled swimming of a flexible plunging foil near a solid wall

Abstract: Numerical simulations are conducted to investigate the influences of a solid wall on the self-propelled swimming of a flexible plunging foil. It is found that the presence of a solid wall enhances the cruising speed, with the cost of increasing input power. Rigid foil can achieve high percentage increase in cruising speed when swimming near a solid wall, but the propulsive efficiency may be reduced. Foils with some flexibility can enjoy the enhancements in both cruising speed and propulsive efficiency. Another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
4
34
2
Order By: Relevance
“…Some of the previous studies observed the increased power input when operating near the ground (Quinn et al 2014a;Dai et al 2016;Tang et al 2016;Park et al 2017). The body kinematics was one of the key parameters in determining the thrust and the power input (Park et al 2017).…”
Section: Fish Swimming Near the Groundmentioning
confidence: 98%
See 4 more Smart Citations
“…Some of the previous studies observed the increased power input when operating near the ground (Quinn et al 2014a;Dai et al 2016;Tang et al 2016;Park et al 2017). The body kinematics was one of the key parameters in determining the thrust and the power input (Park et al 2017).…”
Section: Fish Swimming Near the Groundmentioning
confidence: 98%
“…In the numerical study performed by Ryu et al (2016), a tethered flexible fin with a transverse heaving motion produced an enhanced thrust near the ground. Several studies adopted a self-propelled system to study the ground effect, where the swimming speed and the body kinematics are dynamically coupled (Dai et al 2016;Tang et al 2016;Park et al 2017). Dai et al (2016) and Park et al (2017) modelled a twodimensional (2D) flexible fin swimming near the ground, and the swimming speed increased with the cost of increasing input power.…”
Section: Fish Swimming Near the Groundmentioning
confidence: 99%
See 3 more Smart Citations